Intermodular Communication in Polyketide Synthases: Comparing the Role of Protein−Protein Interactions to Those in Other Multidomain Proteins - Tsuji, Stuart Y; Wu, Nicholas; Khosla, Chaitan (Biochemistry (Easton), 2001)
Although the role of protein−protein interactions in transducing signals within biological systems has been extensively explored, their relevance to the channeling of intermediates in metabolism is not widely appreciated. Polyketide synthases (PKSs) and nonribosomal peptide synthetases (NRPSs) are two related families of modular megasynthases that channel covalently bound intermediates from one active site to the next. Recent biochemical studies have highlighted the importance of protein−protein interactions in these chain transfer processes. The information available on this subject is reviewed, and its possible mechanistic implications are placed in context by comparisons with selected well-studied multicomponent protein systems.